An understanding of Thyroid Problems during Pregnancy - Muhammad Awais Khalid, Asima Munawar, Zoha Mehmood, Zaid Bin Shahbaz, Sohaib Arif, Rida Naz (Pakistan Journal of Medical & Health Sciences, 2022)
Several questions persist, even though our considerate of the connections concerning thyroid function and pregnancy is growing. It is essential to utilize a TSH range for the trimester when evaluating thyroid function during pregnancy. Low TSH levels in the initial trimester should be regarded as natural rather than problematic. TSH levels should not exceed 2.5 mIU/L in the 1st trimester and 3.0 mIU/L in the 2nd and 3rd trimesters. The major form of treatment during the 1st trimester of prenatal period for women with overt hyperthyroidism is PTU therapy. Women with overt hyperthyroidism are highly advised to take anti-thyroid medication. The dosage of LT4 must be increased by 30% to 50% in women who have hypothyroidism and are currently taking it. Pregnant women who have recently been diagnosed with overt hypothyroidism are strongly advised to start on LT4 replacement therapy. Another factor that must be considered is the existence of subclinical hypothyroidism. People with isolated hypothyroxinemia don’t need LT4 therapy, but it’s recommended to protect their thyroids by getting enough iodine. Patients with persistent autoimmune thyroiditis who are euthyroid should not take LT4, although they should still be closely watched because hypothyroidism may set in. The unanswered questions in this area will be addressed by the decisive results of the research, which was just finished and is now being conducted. These uncertainties range from the presence of thyroid antibodies to the management of preclinical hypothyroidism and the usage of LT4 to treat isolated hypothyroxinemia.